Pathophysiological Appraisal of Amlapitta Samprapti - A Contemporary Outlook - Basavarajeshwari B; Gopikrishna S; Vani Nayak; Saranya K (AYUSHDHARA, 2023)
Aim: Critical understanding of the disease Amlapitta by Samprapti Vighatana. The man of this era is becoming more susceptible to series of lifestyle disorders with an unprecedented increase in incidences related to Annavaha Srotas. Amlapitta is one of the commonest Annavaha Srotodushti Vyadhi that closely resembles with hyperacidity in modern science. The altered lifestyle activities i.e., fried food, night shifts, stress, addictions are the major risk factors for Amlapitta. Pitta and Kapha are the main Doshas that get afflicted leading to the formation of Ama due to Agnimandya caused by Mitya Ahara Vihara leading to the stasis of the food in Amashaya. The vitiated Dosha associates with the Ahara Rasa to form Vidagda Ahara, it undergoes Shuktata and cause the Lakshanas of Amlapitta. Various Nidanas acting on the GIT leads to the partial digestion of the food in the stomach and its stasis invites the growth of the bacteria by inhibiting the action of HCL. The impact of hormones and nervous stimulation supports the mechanism leading to the clinical exhibition of symptoms. The critical understanding of the disease manifestation is the fundamental to assess the Nidana majorly driving to the pathogenesis. Methodology: Manual and electronic search of available Ayurveda classics and related articles regarding Amlapitta. Discussion: The analysis of Samprapti of Ama Utpatti and Amlapitta with the contemporary understanding.